(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of pendimethalin on growth and yield of fennel (Foeniculum vulgare Mill.) during 2018-19 and 2019-20 at Bharatpur, Rajasthan. The Pre-emergence application of Pendimethalin 30% EC @ 0.90 kg a.i./ha 2 days after sowing and one hand weeding 60 days after sowing recorded higher grain yield (20.15 q/ha) as compared to the control, i.e. one hand weeding 45 days after sowing (17.75 q/ha). There was 13.52% increase in yield over the control. The technology index value (19.4) was recorded, indicating the gap in potential and demonstration yield due to soil fertility and weather conditions. By conducting on- farm testing of proven technology of weed management, yield potential of fennel can be increased.